Kajian Linguistik Ayat-Ayat Ishraf dalam Al-Qur'an - Al Masithoh, Silvinatin; Al Ghifari, Fahmul Hikam (JADID: Journal of Quranic Studies and Islamic Communication, 2023)
The Qur'an is a miracle whose purity has been preserved to this day. One of the miracles of the Al-Qur'an lies in the beauty of its language, both in terms of its meaning and its words. Even this beauty could not be matched by the Quraysh people who were experts in the field of poetry and language. This research discusses the word form of the word "excessive or Israf" found in the Koran. This article presents a linguistic study of verses related to israf in religious texts, with a main focus on the Al-Qur'an. Israf, in this context, refers to the concept of waste or excessive use of resources. This study aims to analyze the use of language in verses that touch on the topic of israf and how this meaning is constructed and translated in the context of the text. The research method used is semantic and syntactic analysis, with a hermeneutic approach to understand the connotations and social implications of these verses. The findings from this study show that the language used in the verses about israf not only emphasizes the prohibition against waste, but also contains deep moral and social dimensions. This article contributes to a better understanding of how religious texts use language to regulate the economic and social behavior of believers and provides insight into the impact of linguistics on the interpretation of religious teachings. Keywords: Israf, Linguistics, Al-Qur'an, Waste.